2017
DOI: 10.1111/btp.12484
|View full text |Cite
|
Sign up to set email alerts
|

Competitive response of savanna tree seedlings to C4 grasses is negatively related to photosynthesis rate

Abstract: Savanna tree species vary in the magnitude of their response to grass competition, but the functional traits that explain this variation remain largely unknown. To address this gap, we grew seedlings of 10 savanna tree species with and without grasses in a controlled greenhouse experiment. We found strong interspecific differences in tree competitive response, which was positively related to photosynthesis rates, suggesting a trade‐off between the ability to grow well under conditions of low and high grass bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…When we investigated the patterns of Ψ soil in sites where these species occur, we found that the periods (number of days) of water availability are shorter (and less frequent) in sites where A. tortilis is more abundant (Appendix S4). Previous work has shown that A net is strongly related to savanna tree seedlings' competitive ability against grasses (Campbell and Holdo, 2017), suggesting that a strategy like this—which maximizes K max and A net after pulses of water availability—is a particularly adaptive trait for A. tortilis . To our knowledge, this is the first time that physiological measurements at the leaf level (i.e., E ) have been linked to species abundance and the rate of decline in Ψ soil in African savannas.…”
Section: Discussionmentioning
confidence: 92%
“…When we investigated the patterns of Ψ soil in sites where these species occur, we found that the periods (number of days) of water availability are shorter (and less frequent) in sites where A. tortilis is more abundant (Appendix S4). Previous work has shown that A net is strongly related to savanna tree seedlings' competitive ability against grasses (Campbell and Holdo, 2017), suggesting that a strategy like this—which maximizes K max and A net after pulses of water availability—is a particularly adaptive trait for A. tortilis . To our knowledge, this is the first time that physiological measurements at the leaf level (i.e., E ) have been linked to species abundance and the rate of decline in Ψ soil in African savannas.…”
Section: Discussionmentioning
confidence: 92%
“…These water use differences manifest as strong competitive effects of grasses on trees across a wide range of tree life stages. Under both field (February et al ., 2013) and glasshouse conditions (Campbell & Holdo, 2017), competition is highly asymmetric, with grasses exerting a strong competitive effect on tree seedlings while exhibiting little or no competitive response to them.…”
Section: Trees: Competitively Dominant or Simply Survivors?mentioning
confidence: 99%
“…In contrast, when grass productivity and biomass are significantly depressed, droughts can benefit the survival and growth of woody plants both directly by reducing grass competition for limited soil moisture, as well as indirectly by reducing the frequency and intensity of grass‐fueled fires (February et al, ; Higgins et al, ; Morrison et al, ; Scholes & Archer, ). The extent to which tree seedlings are suppressed by grasses also appear to differ between species, with tree species with higher photosynthetic rates suffering greater reductions in biomass in the presence of grasses (Campbell & Holdo, ). Droughts can therefore differentially favour survival and establishment of fast‐growing savanna trees, potentially leading to longer‐term compositional shifts in adult tree communities.…”
Section: Droughts Tree–grass Interactions and The Feedback Effects Omentioning
confidence: 99%
“…The net effects of droughts and disturbances such as fire and herbivory on savanna structure and function is ultimately contingent on the extent to which grass biomass and productivity are suppressed relative to woody plants, which determines both the intensity of tree–grass competition for limited soil moisture as well as the nature of feedback effects arising through changes in fire regimes. Grasses are indeed formidable competitors for soil moisture, and there is ample evidence to suggest that grasses can suppress growth of adult and especially juvenile trees in savannas (Scholes & Archer, ; Sankaran, Ratnam, & Hanan, ; Bond, ; Riginos, ; February, Higgins, Bond, & Swemmer, ; Ward, Weigand, & Getzin, ; Campbell & Holdo, ; Morisson, Holdo, Rugemalila, Nzunda, & Anderson, ). When droughts do not significantly impact grass productivity and biomass, mortality rates of tree seedlings, often vulnerable to grass competition, may be exacerbated.…”
Section: Droughts Tree–grass Interactions and The Feedback Effects Omentioning
confidence: 99%